A bilateral gynandromorph of Tenodera sinensis Saussure, 1871 (Mantodea: Mantidae) from Japan - Oshima, Kazuyuki; Toshima, Kento (Zootaxa, 2024)
This is a first description of a complete bilateral gynandromorph in Mantodea, as well as the first description of a complete gynandromorph of Tenodera sinensis Saussure. This specimen, collected from Kasai-Rinkai Park in Tokyo, Japan, exhibits predominantly male characteristics on the left side of its body and female characteristics on the right side. The left lateral has some features of male, and the notable differences between right and left lateral were found on the antennae, the ocelli, the compound eyes, the forewings and abdominal sternites VII to IX.